MENDETEKSI PENGELAPAN DANA PERJALANAN DINAS DENGAN APLIKASI INTERNAL TICKETING SYSTEM - Christianto, Kevin; Deny, Deny (ISTEK WIDURI, 2020)
Employee official travel activities in a company have an important role in supporting business operations and developing the business wing of the company, especially for large companies that have many branch offices in various regions in Indonesia. With more and more official trips requiring official travel tickets, a system that can internally regulate how tickets are purchased and paid is needed. The system is needed to reduce unnecessary official travel activities and valid data to be compared with data from third-party systems in terms of payment of ticket reservations. Researchers conduct literature studies, interviews, and observations. Literature study conducted by researchers to find the concept of an appropriate methodology to develop the Internal Ticketing System application. Interviews are used to examine important input on the Internal Ticketing System application of several companies that have quite intensive business travel activities, so that they are suitable and useful to be implemented later in the field, and business observations are empowered by researchers to look directly at the ticket booking business process on official trips and conduct individual understanding from researchers. The results of this study were successfully made a prototype of the Internal Ticket System application called Business Travel by using a V-Shaped SDLC method. The prototype making method is more detailed because it has 4 rounds, namely requirements, specifications, high level design and low level unit design.